Climate change induced human displacement in Bangladesh: Implications on the livelihood of displaced riverine island dwellers and their adaptation strategies - Hossain, Babul; Shi, Guoqing; Ajiang, Chen; Sarker, Md. Nazirul Islam; Sohel, Md. Salman; Sun, Zhonggen; Yang, Qi (Frontiers in Psychology, 2022)
Many people are being displaced in Bangladesh's riverine island (char) areas every year due to climate change and its associated natural catastrophes. This study intends to investigate the impact of climate change on internally displaced char people's lives and livelihood along with local adaptation strategies and hindrances to the coping mechanism. Data have been collected from 280 internally displaced households from two sub-districts. A mixed-method approach has been considered combined with qualitative and quantitative methods. The results disclose that frequent flooding, riverbank erosion, and crop loss are the leading causes for relocation, and social relations are impeded in the new place of residence. Increasing summer and winter temperatures, recurrent flooding, severity of riverbank erosion, and expanding disease outbreaks are also the top indicators of climate change identified by displaced people, which is consistent with observed data. It also reveals that around all households come across severe livelihood issues like food shortage, unemployment and income loss, housing and sanitation problems, and so on due to the changing climate associated with disasters between the former and present places. In response to this, the displaced people acclimatize numerous adaptation strategies in order to boost the livelihood resilience against climate change. Still fragile housing and financial condition, lack of own land are the highest impediments to the sustainability of adaptation. Therefore, along with the government, several organizations should implement a dynamic resettlement project through appropriate scrutiny to eradicate the livelihood complications of internally displaced people.